The Struggle Between Chimeric Antigen Receptor T-Cell Therapy and Neurological Complications in Acute Lymphoblastic Leukemia Treatment - Norwin Kubick; Marzena Łazarczyk; Omar Awad; Michał Ławiński; Jarosław Olav Horbańczuk; Mariusz Sacharczuk; Atanas G. Atanasov; Piotr Religa; Michel Edwar Mickael (Current Issues in Molecular Biology)
Acute lymphoblastic leukemia (ALL) accounts for approximately 25% of childhood cancers and 20% of leukemia cases in adults, with a higher prevalence in males than females. It is characterized by symptoms such as fatigue, fever, and bone pain and poses a significant risk of mortality if left untreated. While chemotherapy and stem cell transplantation are standard treatments, their efficacy declines in relapsed or refractory cases, highlighting the need for innovative therapeutic approaches. CAR T-cell therapy has emerged as a transformative technology, offering the potential to overcome these challenges and deliver durable remissions. CAR T-cell therapy demonstrates significant advantages, including targeting specific antigens, overcoming high-risk genetic mutations, and achieving sustained remissions in both pediatric and adult patients. However, notable challenges remain, such as cytokine release syndrome (CRS) and immune effector cell-associated neurotoxicity syndrome (ICANS). In this review, we focus on neurological symptoms associated with CAR T-cell therapy in treating ALL and discuss current and future strategies aiming at reducing their risk.